2003
DOI: 10.1042/bst0311406
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial production of methylglyoxal: a survival strategy or death by misadventure?

Abstract: The production of MG (methylglyoxal) in bacterial cells must be maintained in balance with the capacity for detoxification and protection against this electrophile. Excessive production of MG leads to cell death. Survival of exposure to MG is best understood in the Gram-negative bacteria. The major mechanism of protection is the spontaneous reaction of MG with GSH to form hemithiolacetal, followed by detoxification by the glyoxalase system leading to the production of D-lactate. The KefB and KefC glutathione-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
123
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 23 publications
1
123
0
Order By: Relevance
“…The increased quinone resistance of the ΔqsrR mutant compared with the wild-type strain can be attributed to the enhanced expression of quinone-detoxification genes. SAV2522 and SAV0338, which encode the glyoxalase family proteins that may mediate the thiol-dependent ring cleavage of quinone-S-adducts (40)(41)(42). The homolog of SAV2522 in B. subtilis yfiE indeed possesses metabolic activity of catechol degradation (43).…”
Section: Discussionmentioning
confidence: 99%
“…The increased quinone resistance of the ΔqsrR mutant compared with the wild-type strain can be attributed to the enhanced expression of quinone-detoxification genes. SAV2522 and SAV0338, which encode the glyoxalase family proteins that may mediate the thiol-dependent ring cleavage of quinone-S-adducts (40)(41)(42). The homolog of SAV2522 in B. subtilis yfiE indeed possesses metabolic activity of catechol degradation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Growth inhibition of bacteria occurs when MGO levels in the growth media reaches 0.3 mM and viability decreases at levels above 0.6 mM. Inhibition and loss of activity is a function of cell density and the composition of the growth media [15]. At a concentration > 1.2 mM, MGO inhibited the growth of both Gram-negative and positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of AGE by MGO is well described for eukaryotic cells [10,[22][23][24] but not for bacteria. Booth (2003) identified that the principle events that occurs following cellular exposure to MGO, is the rapid cytoplasmic formation of MGO-GSH adducts, the simultaneous reaction with DNA guanine bases and subsequent activation of DNA repair systems. In addition MGO, reacts with the thiol groups of proteins causing inhibition of enzyme activity [15].…”
Section: Discussionmentioning
confidence: 99%
“…This question of detoxification vs. catabolism also arises for a putative lactoylglutathione lyase (GloA) ( Table 1). In E. coli, GloA is required for detoxification of methylglyoxal, which is known to cause DNA damage (23). Because it has been reported that methylglyoxal is formed during catabolism of certain amino acids and other compounds such as acetone (24), methylglyoxal might therefore also be an intermediate produced upon breakdown of nutrients of the facultative methylotroph.…”
mentioning
confidence: 99%